Pengaruh Brand Ambassador, Kemudahan Penggunaan dan Kepercayaan terhadap Minat Berinvestasi pada Aplikasi Bibit - Septi Herawati; Evan Saktiendi; Lince Afri Yenny; Andi Asnur Pranata Muhibah Hadmar; Wahyu Widjayanti; Ayu Andrianie; Gifari Adam (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
Various technology-based investment applications are developing in Indonesia, one of which is Bibit. This platform offers investments in mutual funds and stocks, which are increasingly popular among the general public. However, several factors still influence investment interest. This study aims to understand the influence of brand ambassadors, ease of use, and trust on investment interest in the Bibit. The method used is quantitative with primary data collected through an online questionnaire to 100 respondents drawn using a purposive sampling technique. Data analysis tools used IBM SPSS Statistics 30 through validity and reliability tests, classical assumption tests, and multiple linear regression tests. The results of this study indicate that partially the brand ambassador and ease of use variables influence investment interest, while the trust variable does not influence investment interest in the Bibit. While simultaneously the brand ambassador, ease of use and trust variables influence investment interest in the Bibit. of the three independent variables, the variable with the greatest influence on investment interest is the ease of use variable which is indicated by the magnitude of the regression coefficient value of 0.369 or equal to 36.9%.